2005
DOI: 10.1093/aob/mci138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Burial in Sand and Water Supply Regime on Seedling Emergence of Six Species

Abstract: Based on these experiments, a 0.5 cm sowing depth resulted in the highest seedling emergence and it is concluded that this is the optimal sowing depth for seedling emergence of all six species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 28 publications
3
69
0
2
Order By: Relevance
“…Water was supplied every three days. To study the influence of water supply on seed germination, 38, 50, 62, 74, 86, or 98 ml of water was supplied each time, corresponding to precipitation levels of 16,21,26,31,36, and 41 mm (Nie and Zheng, 2005;Zheng et al, 2005). To investigate the effect of SAPs on seed germination and seedling growth, 50 ml of water was supplied to mimic the drought condition.…”
Section: Germination Test In the Laboratorymentioning
confidence: 99%
“…Water was supplied every three days. To study the influence of water supply on seed germination, 38, 50, 62, 74, 86, or 98 ml of water was supplied each time, corresponding to precipitation levels of 16,21,26,31,36, and 41 mm (Nie and Zheng, 2005;Zheng et al, 2005). To investigate the effect of SAPs on seed germination and seedling growth, 50 ml of water was supplied to mimic the drought condition.…”
Section: Germination Test In the Laboratorymentioning
confidence: 99%
“…Plant species respond differently to burial depths in seed germination (Chen and Maun 1999, Zheng et al 2005, Li et al 2007. In this study, P. thungergii seeds showed the greatest germination rates at depths of 0.5 and 1 cm (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Many studies on sand dunes have reported that very small seeds showed a high germination rate because of the small amount of moisture required for inhibition (Stairs 1986;Zheng et al 2005). In sand dunes, seed germination is strongly related to available moisture (García et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In sand dune environments, seed germination is strongly related to available moisture and seedling survival is strongly limited by temporal changes in water availability (Maun 2009). Very small seeds showed a high germination rate because of the small amount of moisture required for inbibition (Stairs 1986;Zheng et al 2005). …”
Section: Introductionmentioning
confidence: 99%